Use of Orff Instruments in Musical Education - Kapušin, Maša (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter introduces the use of Orff instruments in music lessons. The main aim is to analyze the contribution and application of Orff pedagogy in the contemporary primary school system. The first subchapter outlines the key principles and fundamental characteristics of Orff pedagogy. The second subchapter focuses on the selection and possibilities of using Orff instruments in the educational process within the subject of musical arts. The findings are supported by contemporary research results.